Laboratory risk assessment of Beauveria bassiana AAD16 on two species of ladybird beetle - Md. Rajib Hasan; Md. Rasel Raju; Un Taek Lim (PLoS ONE, 2025)
Beauveria bassiana AAD16, isolated from Allomyrina dichotoma, shows promise as a mycoinsecticide against various coleopterans. However, assessing non-target impacts on beneficial beetles like ladybirds is crucial before commercialization. Here we assessed the compatibility between ladybird beetles and B. bassiana AAD16. The virulence of the AAD16 strain was compared with that of an available commercial strain, B. bassiana GHA, for two developmental stages (adults and 3rd instar larvae) of two coccinellids, Harmonia axyridis Pallas and Chilocorus spp. Say using the topical (1μl) application method. The ST50 for the two life stages of the two ladybird beetles were not different between the two tested fungal strains. Mycosis rates recorded from the dead bodies were also not significant except in the 3rd instar which showed 36 and 63% from AAD16 and GHA strains in H. axyridis, while those of Chilocorus spp. were 40 and 63%, respectively. In adult stage, the mycosis rates of H. axyridis (males and females tested separately) were (20–23) % and (26–30) % from the AAD16 and GHA strains, while those of Chilocorus spp. (unsexed) were 23 and 30%, respectively. AAD16 caused similar rates of mortality in the adult stages of both species. Therefore, we conclude that B. bassiana AAD16 would not increase risk to these beneficial insects compared to a similar pathogen commercialized.